161Tb-PSMA radioligand therapy in prostate cancer: current evidence and future perspectives - Xiao, Liming; Zhao, Ziyi; Luo, Rui; Liu, Fucen; Hu, Bosen; Zhao, Peng; Yang, Xia; Chen, Zhengguo (Frontiers in Oncology, 2026)
Prostate-specific membrane antigen (PSMA), a type II transmembrane glycoprotein, is overexpressed on the membranes of prostate cancer cells. Lutetium-177 (177Lu)- labelled PSMA-targeted radioligand therapy (PRLT) is employed in treating metastatic castration-resistant prostate cancer (mCRPC) that no longer responds to conventional therapies. However, some patients develop resistance or exhibit limited responsiveness, resulting in disease progression. Terbium-161 (161Tb) shares physical properties with 177Lu, as both isotopes emit β- particles. Notably, 161Tb also emits internal conversion and Auger electrons, offering potential advantages in the effective targeting of small lesions. This dual-emission mechanism enables the treatment of lesions of varying sizes, generating growing interest in 161Tb-labelled radioligand therapy for prostate cancer. This review summarizes current evidence on 161Tb-PSMA, including its mechanism of action, radiolabeling and quality-control procedures, dosimetry, preclinical results, and clinical outcomes, highlighting its therapeutic promise. Future investigations should further validate the safety and efficacy of 161Tb-PSMA radioligand therapy, while enhancing its accessibility and clinical translation.